Assessment of Knowledge and Performance of Village Health Volunteers after Expanding Their Responsibilities in Bago Region, Myanmar, 2017 - Than, Wint Phyo; Nyein, Aye; Thi, Aung (Outbreak, Surveillance, Investigation & Response (OSIR) Journal, 2020)
With declining malaria morbidity in recent years, the National Malaria Control Program, in 2017, expanded Village Health Volunteer (VHV) responsibilities with the integration of other diseases, including dengue haemorrhagic fever, lymphatic filariasis, tuberculosis, leprosy and HIV/AIDS; and changed their name to Integrated Community Malaria Volunteer (ICMV). This study aimed to assess VHV’s knowledge and performance before and after integration and to identify challenges. VHV’s knowledge was assessed with an uncontrolled pre- vs. post-intervention study, and malaria-related performance was assessed with a pre- vs. post-intervention with a non-randomized comparison group. The number of suspected malaria cases blood tested were compared in an intervention township (Kyauktagar) and comparison township (Daik-U). Data were collected by face-to-face interviews and review VHV’s reports and patient registers. The VHV attrition rate was 5% (4/86) over 3 months. All knowledge scores increased significantly after training. However, follow-up knowledge scores were still relatively low. The only difference in reporting status between pre- and post-integration was in timeliness, which was significantly better post-integration. Blood testing was increased in the intervention township. ICMVs had no challenges in malaria activities but some difficulties on reporting forms for other diseases. In conclusion, VHV performance improved in malaria-related aspects after the training. This will support malaria elimination efforts but their performance for non-malaria diseases should be re-evaluated.